On the origin of Goa Cathedral former altarpiece: Material and technical assessment to the work of Garcia Fernandes, Portuguese painter from 16th century Lisbon workshop - Antunes, Vanessa (2019)
Goa Cathedral former altarpiece is one of the oldest set of paintings in India. The seven remaining paintings from the first altarpiece of Goa Cathedral, nowadays in the sacristy, are attributed by some art historians to Master Garcia Fernandes (act. 1514–1565), Portuguese painter from Lisbon workshop. The 16th century was the “Golden age” of Portuguese painting. In this context the Royal Lisbon workshop played a predominant role, where the activity of the painter Garcia Fernandes and his workshop can be distinguished. In this new approach, Goa paintings are being studied and compared with other works in Portuguese territory attributed to this same painter, as St. Bartholomew altarpiece from the chapel of Bartolomeu Joanes in Lisbon Cathedral. The stratigraphic study allowed to compare ground layers, pigments and binders which, were characterized using complementary analytical and imaging techniques: (X-ray Fluorescence spectrometry (XRF), Infrared Reflectography (IRR), Infrared Photography (IRP), Macro Photography (MP), micro-X-ray Diffraction (μ-XRD), Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM-EDS), Raman micro-spectroscopy (μ-Raman), Fourier Transform Infrared micro-spectroscopy (μ-FTIR), Pyrolysis gas chromatography mass spectrometry (PY-GC/MS). This work brought a new insight on the techniques and materials used in this Masterpiece and highlighted the conclusion that Goa Cathedral former altarpiece must be a Portuguese production.